Appraising the need to study on the format of bills of quantities / Shamsulhadi Bandi, Hamimah Adnan and Fadhlin Abdullah - Bandi, Shamsulhadi; Adnan, Hamimah; Abdullah, Fadhlin (Faculty of Architecture, Planning and Surveying, 2016)
There are concerns reported on various aspects of Bills of Quantities (BQ). This includes concerns over the BQ format that helps to organise and convey critical information to parties in construction. Although concerns over the BQ format are mentioned in various literature, these however have been highlighted in fragment. Consequently, there is limited opportunity to demonstrate its enormity, in justifying a study to be conducted. Therefore, by reviewing, analysing and synthesising various issues concerning the uses of BQ, this paper seeks to provide theoretical justification on whether a study to re-examine the BQ format is impending. In adopting to the issues-driven-approach, two objectives were outlined: (1) to critically review the literatures to identify the issues on the application of the BQ; and (2) to synthesise the outcome of the review process to identify relevant research focus. The study which had essentially employed an extensive literature review had synthesised three categories of issues related to: (1) information; (2) format; and (3) working methods. It was found that issues concerning BQ information have been mentioned more frequently in the synthesis. Following the approach, it implies that concerns over BQ format is not considered impending. Rather, a study to re-examine BQ information is much needed and may contribute by offering substantial improvement to the uses of BQ.